Fish Community Structure and Response to Anthropogenic Pressure in the Mangrove Ecosystem of Kladufu Village, East Sorong District - Marice Wakum; Roger R. Tabalessy (INTEGRATED OF FISHERIES SCIENCE, 2025)
The mangrove ecosystem in Kladufu Village, East Sorong District, faces escalating pressure from land conversion and settlement expansion, which threatens to alter estuarine fish community structures. This study evaluated species composition, abundance, and community responses to environmental gradients and anthropogenic stressors in the area. Field sampling was conducted over four weeks using gill nets (1-, 2-, and 3-inch mesh sizes) across two stations representing relatively intact and fragmented mangrove habitats. Concurrent physicochemical measurements were recorded. Ten fish species were documented, primarily belonging to Leiognathidae and Mugilidae. Abundance patterns exhibited a pronounced spatial shift: Station I (salinity 30‰) was dominated by Mugil cephalus (35.9%), while Station II (salinity 20‰, adjacent to residential areas) showed absolute dominance by Aurigequala fasciata (51.5%). Diversity and evenness indices ranged from moderate to low, accompanied by elevated dominance values at the impacted site, indicating community simplification driven by habitat degradation and domestic effluent inputs. Salinity gradients and mangrove conversion emerged as the principal drivers of species distribution. These findings highlight the urgent need for targeted mangrove rehabilitation and ecosystem-based fisheries management to maintain the area’s ecological function as a nursery ground and sustain local coastal fisheries.